Measuring Students’ Empathy and Prosocial Attitudes toward Persons with Disabilities at the Faculty of Social and Political Sciences, Mulawarman University - Aryanti Situmorang; Pipit Afrianti (Soshum: Jurnal Sosial dan Humaniora, 2025)
This study aims to analyse the level of student concern toward children with disabilities at the Faculty of Social and Political Sciences, Mulawarman University. While previous research has discussed empathy or inclusive education separately, few have quantitatively examined the relationship between affective and cognitive empathy and prosocial behaviour among university students at Mulawarman University in East Kalimantan. A quantitative approach using a survey method was employed to measure the dimensions of affective empathy, cognitive empathy, and prosocial behaviour based on the theory of Eisenberg and Miller (1987). A total of 97 students were selected as research samples using the simple random sampling technique. Data were collected through questionnaires and analysed using validity and reliability tests, as well as multiple linear regression analysis. The results indicate that affective and cognitive empathy have a significant influence on students' prosocial behaviour in supporting children with disabilities. The implications of this study highlight the importance of education and socialisation regarding inclusivity to enhance students' social awareness.